2012
DOI: 10.3201/eid1806.111172
|View full text |Cite
|
Sign up to set email alerts
|

Community Survey after Rabies Outbreaks, Flagstaff, Arizona, USA

Abstract: Educational outreach should inform the public about dangers of translocation of wild animals and general aspects of rabies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
(22 reference statements)
4
10
0
Order By: Relevance
“…Similar to findings of a previous study, 4 only 68% (167/245) of respondents in the present study knew that rabies is fatal. Individuals who are not aware of the serious consequences of rabies might not call about possible exposures or seek medical care.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to findings of a previous study, 4 only 68% (167/245) of respondents in the present study knew that rabies is fatal. Individuals who are not aware of the serious consequences of rabies might not call about possible exposures or seek medical care.…”
Section: Discussionsupporting
confidence: 90%
“…4 A Brazos County, Tex, telephone survey conducted during the same year found that dogs aged 4 to 15 months were less likely to be vaccinated against rabies. A 2009 mailed survey of pet owners in Flagstaff, Ariz, found that 96% of dogs, 90% of outdoor cats, and 76% of indoor cats had been vaccinated.…”
mentioning
confidence: 99%
“…Prevention and control can be achieved through strict quarantine measures, elimination of stray dogs, extension program, control of rabies in wild life, registration of dogs and prophylactic vaccination [19]. Human rabies deaths are almost entirely preventable through prompt delivery of post-exposure prophylaxis (PEP) to victims bitten by rabid animals [20,21]. Rabies victims especially from rural areas seek PEP treatment after exhausting the traditional medicinal intervention and usually after loss of a family member [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Dog's petting method by people in Mendoyo assessment of community knowledge of rabies and interactions with animal reservoirs can help target educational messages during the disease control (McCollum et al, 2012).…”
Section: Profile Of Dog Ownermentioning
confidence: 99%